Effect of dephasing on single-qubit rotation gates - Issoufa, Youssouf Hamidou; Messikh, Azeddin (Institute of Physics Publishing (IOP), 2010)
In this paper we investigate the effect of dephasing on the performance of the quantum rotation gate implemented by adiabatic passage and static laser pulses proposed in Lacour et al (2006 Opt. Commun. 264 362). We show that in an open system, where the three-level lambda system is subjected to dephasing of its ground states, the dephasing will introduce additional dynamic phases which cannot be recompensated as in the closed system. We analyse the evolution of the population by using the quantum jump approach. The results are obtained assuming realistic dephasing rates Γ0 1